Effects of Metformin on the Liver and Kidney in Diabetic Patients with Multiple Complications - Al-Ziaydi, Ahmed Ghdhban; Al-Silaykhee, Mohammed Abbas; Aliwi, Ysra Abed Alhasan (Medical Science Journal for Advance Research, 2025)
Background: Diabetes mellitus (DM) is one of the most serious health concerns in the world due to its complicated nature with various health concerns, including liver and kidney damage. Metformin is a commonly prescribed medication for type 2 diabetes and is known for its effectiveness and safety; nonetheless, it does require scrutiny in the presence of liver and kidney diseases. Objective: This study evaluates the concerns related to treatment risk versus benefits of metformin in managing multi-complicated diabetes with special focus on liver and kidney functions. Methods: Metformin’s impact on hepatic and renal parameters were evaluated to formulate key outcomes by measuring liver function tests, kidney functions, and complications like nonalcoholic fatty liver disease (NAFLD) and diabetic nephropathy. Results: Reducing the progression of NAFLD, steatosis, and serum liver enzyme ALT/AST, metformin improves liver health which was supported by its action through AMPK-dependent pathways. In the kidney, micromolar concentrations of metformin appeared to protect renal function, stabilizing and reducing albuminuria in patients suffering from chronic kidney disease (CKD). Alongside these benefits, the risk of lactic acidosis in advanced CKD patients (eGFR < 30 mL/min/1.73m²) and vitamin B12 deficiency presented a need for caution. Longitudinal and meta-analysis studies confirmed that patients with mild to moderate CKD (eGFR ≥30 mL/min/1.73m²) could safely use the drug, provided there is some adjustment in dosage. Individualized dosing remains vital due to the potential harmful effects of gastrointestinal issues such as chronic diarrhea, and the rare occurrence of lactic acidosis. Newer studies underscored metformin’s capability to reduce cardiovascular risks and its impact on personalized treatment, particularly for patients with β-thalassemia major and GDF-15, and ferritin biomarkers indicating relevant de-accumulation of iron overload and complication monitoring. Conclusion: Metformin continues to be an effective medication for diabetes and has positive impacts on the health of the liver and kidneys. Its use is relatively safe in the early stages of CKD and NAFLD but should be used with caution in advanced hepatic-renal failure. A comprehensive approach including genetic and biomarker methods is needed to individualize treatment strategies to maximize benefits. More studies are required to clarify the impact of metformin over an extended period of time, and how to best set criteria for patients with numerous coexisting diseases.